2006
DOI: 10.1590/s0101-31222006000200013
|View full text |Cite
|
Sign up to set email alerts
|

Produtividade e qualidade fisiológica de sementes de feijão em função de sistemas de manejo de solo e adubação nitrogenada

Abstract: O fator climático exerce grande influência na produção de sementes de feijão, porém outros fatores como a ação do ambiente solo, conseqüência de seu manejo, associado à nutrição adequada da planta, principalmente de nitrogênio, podem levar a resultados expressivos tanto no ganho de produtividade como na obtenção de produto de qualidade superior. O objetivo deste trabalho foi avaliar a influência de dois sistemas de manejo de solo (preparo convencional e plantio direto) e da adubação nitrogenada de cobertura (0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
1
7

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 13 publications
2
3
1
7
Order By: Relevance
“…Furthermore, the use of cover crops may lead to an increase of nutrient availability to the parent plant during the period of seed filling, resulting in high quality seeds. As related to the N application effect, similar results were obtained in Farinelli et al (2006), which reported a higher final germination of common bean seeds as a result of high N input. Hampton (2002) reported that proper availability of nutrients (mainly N and P), and water during reproductive stages could increase final germination percentage and subsequently the seedling vigor.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Furthermore, the use of cover crops may lead to an increase of nutrient availability to the parent plant during the period of seed filling, resulting in high quality seeds. As related to the N application effect, similar results were obtained in Farinelli et al (2006), which reported a higher final germination of common bean seeds as a result of high N input. Hampton (2002) reported that proper availability of nutrients (mainly N and P), and water during reproductive stages could increase final germination percentage and subsequently the seedling vigor.…”
Section: Discussionsupporting
confidence: 79%
“…Therefore, even under extreme conditions, common bean seeds presented high quality and vigor. Regardless of cover crop usage, similar results were obtained by Farinelli et al (2006), which reported an increase in seed vigor when high N rates were used. In contrast, Ambrosano et al (1999) and Carvalho et al (2001) did not observe differences in germination rates after accelerated aging when N fertilizer was applied to common bean.…”
Section: Discussionsupporting
confidence: 77%
“…3B). The decrease of the Zn accumulation in the grains could not be explained by the available biological nitrogen, since the nitrogen increase did not necessarily cause an increase in the amount of Zn in the grains, but caused significant increases in the grain yield (Farinelli et al, 2006). …”
Section: Resultsmentioning
confidence: 91%
“…Dentre os fatores limitantes à elevada produtividade, tem-se a utilização de sementes de baixa qualidade (FARINELLI et al, 2006) e a baixa disponibilidade de fósforo (P) nos solos tropicais.…”
Section: Introductionunclassified